Investigation into the effects of static and dynamic stretching on vertical jump performance of taekwondo athletes - Güler, D.; Günay, M. (European Journal of Physical Education and Sport Science, 2019)
This study has sought to illuminate the effect of static and dynamic stretching exercises on the vertical jump performance of taekwondo players. 14 volunteer players were solicited to take part in this study. The participants who were 14-17 age range are licensed players of Amasya Tekhan Sports Club. The protocol employed by Gelen (2008) so as to investigate into the effects of different stretching protocols on the vertical jumping was utilised for tests. Vertical jump tests were conducted on participants three times following each stretching activity in 4-5 min and the best results were noted. Height, body weight and means of BMI, standart deviation, minimum and maximum values of the athletes were measured. A one-way variance analysis in repeated measures (ANOVA) was employed to analyze the data. Findings clearly indicate that neither static nor dynamic stretching exercises have an effect on jumping performance. Correspondingly, this finding may have caused from the physical and psyhological traits of taekwondo players. In summation, based on the analysis in this study, it can be concluded that static and dynamic stretching exercises done after slow aerobic runnings before jumping had no significant effect on front jumping (FJ), squat jumping (SJ) and drop jumping (DJ) performance.